Ways of increasing motivation of students to study foreign language in Technical University - O. A. Bashkirova (Омский научный вестник: Серия "Общество. История. Современность")
The article deals with ways of teaching that contribute to increasing the motivation of students to study a foreign language in a Technical University. The results of the conducted questioning of students on revealing the motives that motivate students of a Technical University to study a foreign language are presented. It is concluded that the main motivating factor is the communicative approach and the involvement of students in speech activity in the studied language